HUBUNGAN POWER OTOT TUNGKAI DAN PANJANG OTOT TUNGKAI TERHADAP KECEPATAN RENANG GAYA BEBAS 50 METER ATLET PEMULA SIGINJAI SWIMMING CLUB KOTA JAMBI - Apsriyani; Ilham; Kurniawan, Alexander (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Freestyle swimming speed in the 50-meter event is one of the main indicators of sprint performance influenced by physical condition and athletes’ anthropometric characteristics. In developing beginner athletes, identifying factors related to swimming performance is important to support the effectiveness of training programs and sports achievement development. This study aimed to analyze the relationship between leg muscle power and leg length on 50-meter freestyle swimming speed among beginner athletes at Siginjai Swimming Club, Jambi City. The study used a quantitative approach with a correlational design. The population consisted of all beginner athletes at Siginjai Swimming Club, and total sampling was applied, resulting in 10 athletes as research samples. Data were collected through a vertical jump test to measure leg muscle power, anthropometric measurements using the difference between standing height and sitting height to determine leg length, and a 50-meter freestyle swimming test to measure swimming speed. Data analysis used descriptive statistics, normality tests, linearity tests, Spearman correlation, and multiple correlation with the assistance of IBM SPSS version 26. The results showed that leg muscle power and leg length had a significant relationship with 50-meter freestyle swimming speed. Simultaneously, both variables demonstrated a strong relationship with sprint swimming performance. This study provides an empirical contribution to the development of beginner swimmer training based on physical condition and anthropometric characteristics.